Cloning, characterization and expression of cellulase-encoding genes in Saccharomyces cerevisiae - Van Rensburg, Pierre,1968- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1996.